OPTIMIZATION OF ONLINE SKCK SERVICES BY THE INTELKAM UNIT TO IMPROVE PUBLIC SERVICES AT KUDUS POLICE REGION - Sri Rohayati, Dharu Melianda (Advances in Police Science Research Journal, 2024)
Requests for SKCK issuance at Kudus Police in the period 2020- 2022 have increased, which is influenced by the growing population of Indonesian society, So that the workforce increasingly requires SKCK as one of the requirements for applying for a job. The National Police through Uryanmin Satintelkam Polres Kudus plays a role in providing SKCK services. One form of SKCK service is the Online system which is a new innovation owned by the Police. However, its implementation is considered less than optimal because there is still a buildup by SKCK applicants at the SKCK service office. This is because there are fewer users of SKCK Online services compared to manual SKCK. This condition is influenced by the lack of public knowledge regarding the existence of SKCK Online services and many do not understand the procedures for using it. The writing of this Final Project aims to find out the implementation of SKCK Online services by the Intelkam Unit of the Kudus Police which is seen from the perspective of management and organizational resources, internal and external factors from the implementation of services as well as supporting and inhibiting factors from the organizational resources owned by Satintelkam Polres Kudus. The writing of this final project uses POAC management theory, organizational resource theory and SWOT analysis theory as an analysis knife and uses the concept of optimization, the concept of public services and the concept of SKCK Online. The approach taken uses a qualitative approach with descriptive analysis and field research data collection techniques with interviews, observations, and document studies. The data analysis techniques used are data collection, data reduction, data presentation and conclusion drawing. The results of the study found that the implementation of SKCK Online services by Satintelkam Polres Kudus was not optimal as seen from the aspects of management and organizational resources owned. This is caused by inhibiting factors in carrying out services, namely internal factors related to the internet network and the SKCK Online service server used are inadequate and external factors regarding the few people who know about the SKCK Online service. Therefore, Satintelkam Polres Kudus has not performed services optimally in accordance with the concept of public services. So it is necessary to solve problems to optimize SKCK Online services in order to improve public services based on the Law, National Police Chief Regulations, and SOP.